2016
DOI: 10.1111/scs.12345
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of constipation among persons living in institutional geriatric‐care settings – a cross‐sectional study

Abstract: The results show that constipation is common among residents in institutional geriatric-care settings in Sweden, which is in line with previous studies from other Western countries. Despite being constipated when having prescribed opioid analgesics, a large number did not have prescribed laxatives. The results indicate the urgency of finding strategies and implementing suitable interventions to improve bowel management in residents in institutional geriatric-care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 38 publications
0
9
1
1
Order By: Relevance
“…Due to differences in definition, the prevalence of constipation in 2007 in the present study (36%) was lower than the prevalence found among the same study population in a previous investigation (67%) [23]. In general, the prevalence of constipation is difficult to compare between different studies because several definitions are used.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Due to differences in definition, the prevalence of constipation in 2007 in the present study (36%) was lower than the prevalence found among the same study population in a previous investigation (67%) [23]. In general, the prevalence of constipation is difficult to compare between different studies because several definitions are used.…”
Section: Discussioncontrasting
confidence: 66%
“…Laxative use has often been used as a marker for constipation, either independently or in combination with other criteria [3, 24]. However, because one of the aims of the present study was to analyze the use of these drugs, we chose not to include laxatives in the definition, and this is the reason why the prevalence is lower in the present study compared to the study mentioned above [23]. In clinical practice, constipation is often defined as fewer than three bowel movements per week [25] and this symptom was also the only single symptom that increased significantly between the years in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…A study showed that in partially institutionalized elderly people, the prevalence of constipation was 67% 27 . In addition, fibers are involved in improved postprandial glycemic response, cholesterol control and cardiovascular risk reduction 13 .…”
Section: Resultsmentioning
confidence: 99%
“…Ponadto, blisko 15% populacji geriatrycznej wymaga stosowania leków ułatwiających wypróżnianie [4]. Wśród pacjentów w starszym wieku, którzy wymagają hospitalizacji, 67% zmaga się zaparciami o podłożu czynnościowym [5]. W badaniu z 2020 roku Deb i wsp.…”
Section: Wprowadzenieunclassified